PASADO Y FUTURO DE NUESTRA SOCIOLOGÍA - Ruiz Restrepo, Jaime (La Sociología en sus Escenarios, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Abstract. Professor Jaime Ruiz Restrepo in his article the past makes a route by and future of the Colombian sociology, in which he evaluates the courses by which the discipline has journeyed, in its academic expression and it raises mainly that it has sense to take a break to correct errors, to renew proposals and to try new ways, from the University, that has been its natural means. It affirms that the process of formation of sociologists in the country has been tie from the beginning with the research work and that the institutionalization of the investigation is the premise for the recognition of Sociology inside social sciences. Nevertheless, in the social investigation methodological theoretical approaches have also faced both. On the one hand, the empiricist who stood out with the theoretical model and methodological functionalist - fusion of the traditions European and American, which is the departure point of a great amount of investigations of all the quality levels, but that as memory Towers are counted from texts of Priest Camilo Torres and Fals Borda, in the decade of the years 60 and beginnings of the 70. On the other hand, the structuralism and Marxist approaches. Thus, kindness and deficiencies of the Marxism, or the structuralism, or the functionalism, have not been assimilated correctly in their historical contents, so that the allegiances to a u others have been of rupture and very usually of touching nature and without proving their scientific effectiveness. In our means, in the formation and the development of the research work, this process was lived clearly and for this reason, the production of sociological works appeared strongly influenced by political positions. The investigation that was tried to develop at that time filled of disquisitions around the nature of the theoretical approaches and of extensive expositions about the historical processes, which, in last, diminished "research problems". The future of Sociology. Most evident it is than conditions for the consolidation of a serious sociological work based on the research activity exist. Nevertheless, the challenge continues being that the social sociologists and the other scientists we must continue demonstrating how our analyses indeed lead to the understanding of real collective problems and allow the formulation of possible solutions, that is to say, that the instruments that we used and the consequent theoretical rigor allow to the societies car to know themselves, to evaluate the extension of their social problems and to formulate feasible projects. In this sense, also we can accept that progressively Sociology has come emphasizing its hermeneutics aspect, to take reading and to interpret the sense of social texts and the situations, and is indeed there, where the qualitative investigation and micro sociology also acquire great value with their histories of life and the analysis of the daily life. It seems that the sociologists have reclaimed the sociological language, developing it around a set of paradigms. The challenge is to cause that language enunciates proposals around the social facts with relatively ample criteria of reliability, which is equivalent to say, that a confrontation spirit is due to maintain, where the slight knowledge apparently used logics and commonly, such as those of " structure, action, system, function and class social" they subject to the verification. Resumen. El Profesor Jaime Ruiz Restrepo en su artículo hace un recorrido por el pasado y futuro de la sociología colombiana, en el cual evalúa los rumbos por los cuales ha transitado la disciplina, en sus expresión académica y plantea que tiene sentido hacer un alto para corregir errores, para renovar propuestas y para ensayar nuevos caminos, sobre todo desde la Universidad, que ha sido su medio natural. Afirma que el proceso de formación de sociólogos en el país ha estado vinculado desde el comienzo con la labor investigativa y que la institucionalización de la investigación es la premisa para el reconocimiento de la Sociología dentro las ciencias sociales. Sin embargo, en la investigación social se han enfrentado también los dos enfoques teóricos metodológicos. Por un lado, el empírico que se destacó con el modelo teórico y metodológico funcionalista -fusión de las tradiciones europea y americana-, lo cual es el punto de partida de una gran cantidad de investigaciones de todos los niveles de calidades, pero que como recuerdo se cuentan a partir de los textos del Padre Camilo Torres y de Fals Borda, en la década de los años 60 y comienzos de los 70. Y, por el otro, los enfoques marxistas estructuralistas. Así, las bondades y deficiencias del marxismo, o del estructuralismo, o del funcionalismo, no han sido asimiladas correctamente en sus contenidos históricos, de manera que las adscripciones a unos u otros han sido de ruptura y muy usualmente de naturaleza emotiva y sin probar su eficacia científica. En nuestro medio, en la formación y en el desarrollo de la labor investigativa, se vivió claramente este proceso y por ello, la producción de trabajos sociológicos apareció fuertemente influenciada por posturas políticas. La investigación que se intentó desarrollar en esa época, se llenó de disquisiciones en torno a la naturaleza de los enfoques teóricos y de extensos planteamientos acerca de los procesos históricos, lo cual, en últimas, minimizaba el "problema de investigación". El futuro de la Sociología. Lo más evidente es que existen condiciones para la consolidación de un trabajo sociológico serio basado en la actividad investigativa. Sin embargo, el reto sigue siendo que los sociólogos y los demás científicos sociales tenemos que seguir demostrando cómo nuestros análisis efectivamente conducen a la comprensión de problemas colectivos reales y permiten la formulación de soluciones posibles, es decir, que los instrumentos que utilizamos y el rigor teórico consecuente permite a las sociedades auto conocerse, evaluar la extensión de sus problemas sociales y formular proyectos factibles. En este sentido, también podemos aceptar que progresivamente la Sociología ha venido enfatizando su aspecto hermenéutico, de hacer lectura e interpretar el sentido de los textos sociales y de las situaciones, y es precisamente allí, en donde la investigación cualitativa y la micro sociología adquieren también gran valor con sus historias de vida y el análisis de la vida cotidiana. Parece que los sociólogos han recuperado el lenguaje sociológico, desarrollándolo alrededor de un conjunto de paradigmas. El reto es hacer que ese lenguaje enuncie proposiciones en torno a los hechos sociales con criterios de fiabilidad relativamente amplios, lo que equivale a decir, que se debe mantener un espíritu de confrontación, en donde las nociones aparentemente lógicas y utilizadas corrientemente, tales como las de "estructura, acción, sistema, función y clase social" se sujeten a la verificación.